2020
DOI: 10.1080/21691401.2019.1709863
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-antioxidant impacts of circZNF609 silence in HaCaT cells through regulating miR-145

Abstract: Background: CircZNF609 (cZNF609) is previously revealed as an essential mediator in oxidative stress. This paper determined the role of cZNF609 in skin oxidative damage to evaluate its importance in pressure ulcer. Methods: HaCaT cells treated by H 2 O 2 were considered as a cell model of pressure ulcer. The role of cZNF609 in the model was checked by conducting CCK-8 assay, FITC-PI double-staining, ROS detection and Western blot. The downstream gene and signalling of cZNF609 were studied by utilizing qRT-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…When hydrogen peroxide-injured keratinocytes were treated with circular RNA ZNF609 silencer, there is an upregulation of miR-145. This increase in miR-145 resulted in lower ROS generation, decreased keratinocyte p53 and caspase 3 expression, and improved cell viability [87]. When miR-145 was silenced, there was a loss of anti-oxidant effects.…”
Section: Mirna Regulation Of Oxidative Stress In Pressure Ulcersmentioning
confidence: 96%
See 2 more Smart Citations
“…When hydrogen peroxide-injured keratinocytes were treated with circular RNA ZNF609 silencer, there is an upregulation of miR-145. This increase in miR-145 resulted in lower ROS generation, decreased keratinocyte p53 and caspase 3 expression, and improved cell viability [87]. When miR-145 was silenced, there was a loss of anti-oxidant effects.…”
Section: Mirna Regulation Of Oxidative Stress In Pressure Ulcersmentioning
confidence: 96%
“…When miR-145 was silenced, there was a loss of anti-oxidant effects. miR-145 inhibits JNK and p38-MAPK signaling pathways, which are activated by ROS [87,121]. JNK has been shown to have a complex role in pressure ulcer pathophysiology, increasing ROS production but inhibiting apoptotic activity [84,87,121].…”
Section: Mirna Regulation Of Oxidative Stress In Pressure Ulcersmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers found that in HaCaT cells treated with H 2 O 2 , which were considered a cell model of pressure ulcers, circZNF609 silencing may reduce oxidative stress by regulating miR-145 [106]. CircNFIX is abundant, conservative, and stable in H9c2 cells.…”
Section: Circrnas Regulate Various Diseases Via Modulatingmentioning
confidence: 99%
“…Skin oxidative damage is considered to be the main factor in the pathogenesis of PU. 26,27 Therefore, recent studies reported that antioxidant drug have been considered as potential agents for improving the treatment of PU for clinical application. 10,28,29 Moreover, we recently demonstrated the usability of OKD48 mice to quantify the oxidative stress level using cutaneous I/R injury mice model.…”
Section: Dmf Suppressed Ros Production Caused By Oxidative Stress Imentioning
confidence: 99%